Efektivitas Pelayanan Publik Di Kantor Pertanahan Kota Manado - Nensi Margaret Juliana Runturambi; Theodora M. Katiandagho; Grace A. J. Rumagit (AGRI-SOSIOEKONOMI, 2022)
This research aims to analyze the effectiveness of public services at the Manado City Land Office. The analytical method used in this research is quantitative analysis with a descriptive approach. The results of Kantah Manado City's research get a "B" service quality with a "Good" performance category, which means that the effectiveness of community satisfaction from the results of public services from July to December 2021 is categorized as "Good". Even though the results of the community's assessment of public services in Kantah Manado City are good, strategies and efforts from service providers are still needed to improve the three service elements that get bad and bad scores and maintain or improve the service elements that are already good to be very good ideal assessments. The conclusion of Kantah Manado's research based on the Community Satisfaction Index using an assessment of 9 elements of public service getting a score of 77.61 with a good performance category and service quality "B" but still needs strategies and efforts from service providers to improve the three service elements that get bad and poor scores. good and maintain or improve the service elements that are already good into an ideal assessment of very good.